2020
DOI: 10.1007/s40279-020-01295-8
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Maintaining Metabolic Health During a Global Pandemic

Abstract: The ongoing global pandemic brought on by the spread of the novel coronavirus SARS-CoV-2 is having profound effects on human health and well-being. With no viable vaccine presently available and the virus being rapidly transmitted, governments and national health authorities have acted swiftly, recommending 'lockdown' policies and/or various levels of social restriction/isolation to attenuate the rate of infection. An immediate consequence of these strategies is reduced exposure to daylight, which can result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 50 publications
0
77
0
5
Order By: Relevance
“…While the impact of the COVID-19 pandemic and its related social restrictions are still yet to be understood, early studies have shown that it has far-reaching effects on psychological and physical health in children and adolescents. Moreover, COVID-19-related restrictions likely exacerbate the current public health problems of low levels of physical activity and high prevalence of sedentary behaviors in children and adolescents [ 50 ]. Considering much of the current literature is comprised of survey data or commentary discussion at this time, more research examining lifestyle changes with objective measures such as accelerometry are warranted.…”
Section: Resultsmentioning
confidence: 99%
“…While the impact of the COVID-19 pandemic and its related social restrictions are still yet to be understood, early studies have shown that it has far-reaching effects on psychological and physical health in children and adolescents. Moreover, COVID-19-related restrictions likely exacerbate the current public health problems of low levels of physical activity and high prevalence of sedentary behaviors in children and adolescents [ 50 ]. Considering much of the current literature is comprised of survey data or commentary discussion at this time, more research examining lifestyle changes with objective measures such as accelerometry are warranted.…”
Section: Resultsmentioning
confidence: 99%
“…While this strategy was largely successful, its negative effects will be of consequence to the health of youth, as for four months they were out of school and for the most part, stuck in the confines of their homes. 1 With these lockdowns comes the possibility of weight change that may be associated with amplified stress, depression, anxiety, sedentary time, unhealthy dietary habits, and more, reducing the negative impacts of lockdown on the general public has attracted global attention.…”
Section: Introductionmentioning
confidence: 99%
“…1 C and 1D). Considering the maintenance of physical activity levels and nutritional status reported in those studies [3] , [6] , our findings suggest that body fat is likely to be increased during COVID-19 restriction, potentially adversely affecting metabolic health and disease prognosis [7] . Although there is evidence that patients on AST may be less likely to develop COVID-19 than PCa patients not receiving AST [8] , poor body composition and reduced physical activity levels can contribute to poorer disease prognosis, altering systemic and cellular factors and increasing the incidence of comorbidities such as diabetes or hypertension [9] .…”
mentioning
confidence: 65%